2018
DOI: 10.1177/0040517518817060
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-roll electrochemical fabrication of non-polarizable silver/silver chloride-coated nylon yarn for biological signal monitoring

Abstract: The main goal of this work is to develop a fabrication process and system for silver/silver chloride (Ag/AgCl)-coated yarn, as Ag/AgCl is the preferred non-polarizing material for interfacing with the body in a clinical setting when monitoring biological signals. A roll-to-roll electrochemical system was designed and built to deposit AgCl on Ag-coated nylon 6,6 yarn in a controllable process. In particular, the movement of the yarn, voltage limit and mixing of 0.9% sodium chloride solution were held constant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The method used to fabricate Ag/AgCl yarns is a modified setup from previous work 12 . The setup allows for a higher throughput of Ag/AgCl yarn, as well as modifiable process parameters, which allow for accurate control of coating thicknesses and yarn conductance to meet material performance requirements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method used to fabricate Ag/AgCl yarns is a modified setup from previous work 12 . The setup allows for a higher throughput of Ag/AgCl yarn, as well as modifiable process parameters, which allow for accurate control of coating thicknesses and yarn conductance to meet material performance requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts have been devoted to developing dry electrodes for biosignal monitoring, such as printed Ag/AgCl-based inks on flexible substrates or textiles 4 , 10 . Work by Xu et al 11 and Haddad et al 12 have demonstrated the fabrication of Ag/AgCl based e-textiles comparable with Ag/AgCl solid gel electrodes for biosignal monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plating, dip-coating, physical vapor deposition, polymerization of conducting polymers, knitting, weaving and embroidery, inkjet, screen, and stencil printing are used [168]- [171]. Roll-to-roll electrochemical fabrication of Ag/AgCl coated nylon yearns has been demonstrated [172], and screen and stencil printing and blade coating have been combined for wearable EIT electrode arrays on polyester fabrics [173]. Along with silver, PEDOT:PSS (with additional crosslinkers for improved properties) is playing a prominent role with textile electrodes as well [171], [174].…”
Section: Recent Advancements In Bioimpedance Sensor Realizationmentioning
confidence: 99%
“…In particular, metal coated nylon fibers have been broadly applied in wearable sensors, such as strain sensors, 40 conductive resistive sensors, 41 pressure sensors, 42 and biological sensors. 43 In addition, noble metal coated nylon fibers with a rough surface provide the possibility to be used as wearable high-sensitive SERS substrates due to the facilitation of building dense plasmonic hotspots. In this work, coarse silver (Ag) layer coated nylon fibers (NFs) with twisted spiral structure are used to load gold (Au) nanoparticles (NPs) to fabricate ultrasensitive SERS substrate (denoted as Au NP@Ag/NF) in a relatively simple and low-cost technique.…”
mentioning
confidence: 99%